A clinical guide to pediatric infectious disease - Janner, Donald (LWW medical book collection., 2005)
The ideal time-saver for busy clinicians, this handy guide delivers a practical ""how-to"" perspective on diagnosis and treatment for a range of commonly encountered childhood infections-from otitis media, sinusitis, and urinary tract infection ... to hepatitis, cervical adenitis, pediatric tuberculosis, pneumonia, catheter infection, and more. Coverage includes clinically essential material on specific drugs, dosages, and drug interactions, a section on accurate interpretation of laboratory tests, and guidelines on infection control in organ transplant recipients. A consistent chapter template